Analysis of Gymnastics Activities in Stimulating Gross Motor Development in Early Childhood - Siti Khoiriyah; Heriestia Salma Rizky Khairani; Rahmiati R; Anna Nadha Khilma Inthaha; Annafi’ Nurul ‘Ilmi Azizah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Gross motor development is an important aspect of early childhood growth that needs to be stimulated through physical activities appropriate to children’s developmental stages. Gymnastics activities are considered an effective form of stimulation because they can improve body coordination, balance, agility, and muscle strength in children. This study aims to describe teachers’ understanding of gross motor development in early childhood, the implementation of gymnastics activities, children’s responses, as well as the obstacles and strategies used by teachers in stimulating children’s gross motor skills. This study employed a qualitative descriptive approach. The research was conducted at RA Amanah Ummah Wonosari Klaten with 15 children and classroom teachers as the research subjects. Data were collected through observation, interviews, and literature studies. The data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The results showed that gymnastics activities were able to improve children’s gross motor skills, such as walking, jumping, maintaining balance, and coordinating body movements. Children appeared enthusiastic and active during the activities. Teachers applied several strategies, including rhythmic gymnastics, movement and songs, and direct movement demonstrations. However, the implementation still faced obstacles such as limited time, space, and differences in children’s motor abilities